Advancement on nanoparticle-based drug delivery systems for cancer therapy - Mishra B.; Upadhyay M. (My University, 2025)
Nanotechnology has brought a great revolution in cancer detection, screening, and imaging through its various novel innovative nanodelivery systems. Tracking of cancerous site and cells via in vivo imaging using excellent nano tools or modifying the nano tools in a different way is the greatest achievement toward advancement in nanoparticle-based cancer therapy. Anticancer drugs used in chemotherapy cause severe adverse effect due to its high-dose requirement; however, the advent of nanotechnology and drug delivery at nanoplatform has lessen this to an extent. The nanotechnology-based drug delivery systems due to their specificity, selectivity, and sensitivity target the site of interest in a programmed manner without harming the healthy tissues. In addition, quantum dots, gold nanoparticles, carbon nanotubes, etc., are advanced nanodevices that have emerged out as promising tool in cancer imaging and diagnosis. The present chapter summarizes the advanced progress and application in nanotechnology for cancer diagnosis and imaging. © 2021 Elsevier Inc. All rights reserved.